Pillow talk [videorecording (DVD)] - Gordon, Michael, 1909-1993; Hudson, Rock, 1925-1985; Day, Doris, 1922-2019-; Randall, Tony; Ritter, Thelma (Universal Studios : [Distributed by] Universal Studios Home Entertainment, 2009)
Tells the story of an uptight interior decorator who must share a party line with a laid-back playboy. But the real connection is made when the two meet and he starts wooing her with late-night calls while pretending to be someone else.